STUDENT PROFILE OF PANCASILA IN ENGLISH LANGUAGE TEXTBOOKS FROM DIFFERENT PUBLISHERS: A CONTENT ANALYSIS STUDY - Permatasari, Chindy Yulia; Yunita, Wisma; Harahap, Alamsyah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
The textbooks published in the Merdeka curriculum edition have been prepared based on the Pancasila Student Profile to strengthen Pancasila-based character education. However, English textbooks published by different publishers tend to display western cultural values which can contribute to reducing the character values of Pancasila. For this reason, this research was carried out with the aim of finding out how far the values of the Pancasila student profile are integrated in English textbooks, and to find out teachers' views on books that integrate the values of the Pancasila Student Profile. This research used mixed methods with data sources from two Merdeka curriculum English textbooks are Bahasa Inggris;Tingkat lanjut and Pathway to English for class XI high school and 3 English teachers who used English books published by the Ministry of Education and Culture and the Erlangga publisher. The research instrument is document analysis checklist prepared based on a grid of results from the six values of the Pancasila Student Profile and interviews about Pancasila values which have been integrated in the book used. The results of quantitative research show that books published by the Ministry of Education and Culture are integrated (72%) and books published by Erlangga are very integrated 81%). The most prominent integrated value in each book is the Critical Thinking dimension which is most prominent, especially in the exercise section. Meanwhile, the independent dimension is the least integrated. Second, the results of teacher interviews show that the highest percentage of integrated Pancasila profile values of students are in the dimensions of faith, fear of god almighty, and noble morals in the second book already presents how students should, by writing letters of gratitude and folk tales about disbelief while in the independent dimension the lowest percentage of integration, this is because the integration of Pancasila student profile values is less concrete and less varied in the application of Self and Situation Understanding and Self-Regulation in everyday life. In conclusion, the integrated scores of the Pancasila student profile in both English textbooks are integrated with different percentage integration levels in each book. This study recommends that book compilers can increase the frequency of the presence of Pancasila student profile values in books, both in terms of content, exercises and visuals.